Análisis socioeconómico y su impacto en la pandemia Covid-19 de las Pymes Comerciales del cantón La Maná. - Bautista Chiluiza, Luis Gustavo (2022)
Small and medium-sized commercial enterprises (SMEs) play an important role in the economic development of our country. The motivation that led to conducting the research is based on the problems in which they are immersed with respect to the global pandemic of Covid-19. The objective is to know the impact of the socioeconomic factors caused by the Covid-19 pandemic on the commercial SMEs in the canton of La Maná. The direct beneficiaries of the research are the owners and collaborators of the commercial establishments, and the indirect beneficiaries are the governmental organizations and others interested in knowing the subject. The methodology for the execution of the project is formative research, bibliographic research, and field research. The research methods are deductive and analytical. In addition, Cronbach's alpha was applied through the SPSS statistical system to demonstrate the reliability of the instrument. The instrument used was the survey. The study population is made up of 1,760 companies in the commercial sector registered in the Fire Department of La Maná. To establish the sample, finite population sampling was used, considering a 5% error rate and a confidence level of 95%, and a sample of 326 commercial businesses. A stratified sample was used to identify the number of businesses and their activities. The results were that in relation to previous years, social factors were affected by 80.1%. In the same line, economic factors were affected by 71.8% of commercial businesses in the canton.